Foreign Language and Individualization of Student Training: Realities, Trends, Options - Irina V. Leushina; Igor O. Leushin (Moscow Polytechnic University, 2019)
The article discusses the features of the modern system of Russian higher education, reveals its advantages and disadvantages. In the light of the Federal Target Program for the De velopment of Education for 2016-2020, the authors conclude that the multifunctional foreign language communicative competence plays a special role in the process of forming a holistic competence-based portrait of a graduate of a higher educational institution, considering the three main trends characteristic of the transition to an updated educational system: direct participation in the educational process of all stakeholders (students, teachers, representatives of professional communications, employers); the need to create and operate an innovative information and educational environment, taking into account the possibility of modeling real professional tasks; personal orientation and individualization of the preparation of students with the growing role of the learner in the educational process. The task is to find the best methodological tools and organizational forms of educational activities in the context of foreign language training of university students. In accordance with this, the authors propose options for implementing the formulated trends. Particular attention is paid to the possibilities of interactive learning of foreign languages; the peculiarities of «immersion» of students in a model professional environment with the involvement of employers and representatives of professional communities, including as experts, in direct participation in the educational process; the importance of personal communication between students and other subjects of the educational process; work in small groups. The emphasis is on the need to create favorable conditions for self-education and self-realization of future graduates and an individual approach to each of them.